Shrimp Farmer’s Perceptions and Adaptation Strategies to the Threat of Climate Change in Bangil District, East Java - Fatahullah, Fatahullah; Toiba, Hery; Sujarwo, Sujarwo (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
As one of the main stakeholders in the fishing industry, shrimp farmers are directly affected by climate change that causes changes in seawater temperature, rainfall, and unpredictable weather patterns. Related to the issue, the threat to income may be felt by shrimp farmers. Therefore, in this study, we highlight two objectives as a basis for drawing up this article, namely (1) to understand shrimp farmers’ perceptions of climate change, and (2) to identify factors that influence farmers’ decisions in implementing adaptation strategies. There are two types of analysis that we use, namely descriptive analysis and logit regression analysis. Our findings show that the majority of shrimp farmers consider climate change manifested in the form of changes in rainfall patterns (96.21%), increases in pond water temperatures (98.71%), decreases in yield production (95.41%), and increases in shrimp pests and diseases (96.23%). The results of our logit regression analysis show that the decision-making factors of shrimp farmers are significantly influenced. These results indicate that the implementation of adaptation strategies in the fisheries sector can generate significant growth and reduce the risks posed by climate change. As a result, the government needs to encourage the development of more suitable climate change adaptation strategies for small-scale shrimp farmers in Indonesia.